Comparative study on behaviour of cable-stayed bridge with normal support and spring controlled system - Ma, Hnin Ei Cho; Tin , Tin Win (2008)
The main objective of this research is to study the damped spring controlled system to reduce the earthquake-induced forces in the structure of cable-stayed bridges by applying STAAD-Pro structural analysis. The total length of the proposed cable-stayed bridge is 450 ft from abutment to abutment. It has symmetrical span arrangement with 250 ft (main span length) and 100 ft (each of side span length) respectively. It consists of dual H-type tower and the warren truss type steel girder. The girder has 10ft each panel bays and 5ft in height. A reinforced concrete, H-type tower, rises 50 ft above the truss girder base. Its apex is 15 ft high in pylon that supports a dual-plane cable system. Two pairs of cables on each side are arranged as a fan type cable system. Cables are installed from the outermost cable connections; from the ends of the bridge to the tower with 50 ft spacing to distribute axial load throughout the deck. HS 20-44 AASHTO loading will be applied. Effects of impact loading, wind loading, temperature forces and horizontal seismic loading will also be considered. Firstly, the static analysis of cable-stayed bridge is accomplished without considering the effect of earthquake forces. After that the spring supports are installed between tower and girder for effective flexible responses of the cable-stayed bridge due to the horizontal earthquake forces only. The intelligent control system is used to guarantee the relative movements between the connected structural parts. The bridge is analyzed and designed by using the STAAD-Pro engineering software in this study. The materials and loads are specified according to the AASHTO specifications. This study provides the proof of seismic protection and the comparative results of the controlled and uncontrolled structural system such as tower deformations, truss girder axial forces, cable axial forces, truss girder displacement and support reactions.